DESIGN DE DISPOSITIVOS VISUAIS: DIRETRIZES PARA O CONTEXTO BRASILEIRO E DISPOSITIVOS EXISTENTES - Moura, Paula K. de; Cavalli, Camila Bettoni; Rocha, Cecilia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In-home displays can save energy by providing users with real-time information on their consumption. Previous studies have shown that the design of such devices plays an important role in effectively communicating such information to users. This paper indicates information elements best suited to the Brazilian context for adults. Guidelines are proposed based on the results of four focus groups, which are then compared to existing displays on the market. It is concluded that none of the existing devices fully meets the proposed guidelines, since Brazilian users need additional information about their consumption.